Pengaruh Strategi Pikir Plus menggunakan Metode Outdoor Study terhadap Keterampilan Menulis Puisi Kelas VIII SMP Darul Hikam - Mualifah, Siti; Zuhdi, Rasyid (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Writing ability is one of the skills that must be mastered by grade VIII students in Indonesian language learning. Students’ ability to master the vocabulary and spelling of the words they use to express their ideas is very important in writing poetry. Based on the results of observations at Darul Hikam Junior High School, it shows that there are still student obstacles in writing poetry in class so that students feel less effective in expressing their ideas and objects. In addition, teachers still use traditional Indonesian language learning methods with teacher-related approaches in daily teaching and learning activities. A teacher’s skill in choosing effective learning strategies and methods can improve students’ poetry writing skills. Learning methods and strategies that increase students’ poetry writing skills are the Think Plus Strategy with the Outdoor Study Method. This study aims to find and explain the impact of thinking and strategies using the outdoor study method on grade VIII students of Smp Darul Hikam Kuwarasan in the 2023/2024 academic year. The method applied in this research is experimental method with one group pretest and posttest design. The sample in this study was formed from 24 students. Normality and homogeneity testing using the SPSS application illustrates the significance value of Sig. 0.571 > 0.05 and 0.412 > 0.05 illustrating that the class is normally distributed and homogeneous. Data on learning outcomes were analyzed using paired sample t-test with 5% confidence level. Based on the results of the SPSS test, the Sig (two-tailed) significance value is 0.032 <0.05, so it can be said that the strategy of thinking plus with the outdoor study method has a significant effect on improving the poetry writing skills of students in grade VIII of Darul Hikam Kuwarasan Junior High School in the 2023/2024 academic year.